The Use of Animation Film in Writing Skill at Junior High School: Penggunaan Film Animasi dalam Keterampilan Menulis di Sekolah Menengah Pertama - Adiningtyas, Widya; Santoso, Dian Rahma (Universitas Muhammadiyah Sidoarjo, 2023)
Writing is one of the difficult skills for students because it requires the ability to express ideas, thoughts and feelings. This study discusses the use of animated film in learning recount text writing skills for 8H grade students at SMP Negeri 2 Gempol. The purpose of this study was to determine the effect of using animated film on the ability to write recount text. The method used in this study is quantitative with a pre-experimental design that applied pre-test and post-test instruments. By using the paired sample T-Test, it shows that there are differences in the results of the average scores of the pre-test and post-test, namely 61.41 for the average value of the pre-test, and 75.63, for the post-test. This shows that the use of animated films has an influence in learning writing skills.